KERANGKA INVESTIGASI FORENSIK WHATSAPP WEB DAN TELEGRAM UNTUK HACKING INVESTIGATION - Syukriadi; Romy Aulia; Melissa Triandini; Amrizal (Smart Education, 2026)
Abstract: Instant messaging platforms are frequently involved in cyber incidents, including attacker coordination, credential sharing, and post-compromise extortion. This study develops a digital forensic investigation framework for WhatsApp Web and Telegram to support hacking investigation through artifact mapping, evidence acquisition, and chain of custody management. The method uses a focused literature review, scenario-based investigation design, and comparative analysis of artifacts across browser, operating system, and application layers. The results produce an artifact taxonomy, an acquisition decision matrix covering logical, file-system, and memory approaches, and concise standard operating procedures to preserve evidence integrity, traceability, and reproducibility. The proposed framework can support institutional incident response teams, internal investigators, and digital forensic practitioners in improving evidence quality and investigation effectiveness. Keywords: Digital Forensics; Whatsapp Web; Telegram; Chain of Custody; Cyber Incident. Abstrak: Aplikasi pesan instan sering terlibat dalam insiden keamanan siber, termasuk koordinasi serangan, distribusi kredensial hasil kompromi, dan pemerasan pascainsiden. Penelitian ini mengembangkan kerangka investigasi forensik digital pada WhatsApp Web dan Telegram untuk mendukung hacking investigation melalui pemetaan artefak, akuisisi bukti, dan pengelolaan chain of custody. Metode yang digunakan berupa studi literatur terarah, perancangan skenario investigasi, dan analisis perbandingan artefak pada lapisan browser, sistem operasi, dan aplikasi. Hasil penelitian menghasilkan taksonomi artefak, matriks keputusan akuisisi yang mencakup pendekatan logis, file- system, dan memori, serta prosedur operasional ringkas untuk menjaga integritas, keterlacakan, dan reprodusibilitas bukti. Kerangka yang diusulkan dapat membantu tim respons insiden, penyidik internal, dan praktisi forensik digital dalam meningkatkan kualitas bukti dan efektivitas investigasi. Kata Kunci: Digital Forensics; Whatsapp Web; Telegram; Chain of Custody; Insiden Siber